Developing a model for an agile supply chain in pharmaceutical industry - Mehralian, Gholamhossein; Zarenezhad, Forouzandeh; Rajabzadeh Ghatari, Ali (International journal of pharmaceutical and healthcare marketing, 2015)
Purpose – The purpose of this study is to develop a model for an agile supply chain in the pharmaceutical industry. In a continuous changing global competitive environment, an organization’s supply chain agility directly impacts its ability to produce and deliver novel products to its customers in a timely and cost-effective manner. While the beneficial effect of supply chain agility is generally appreciated, the literature addressing how a pharmaceutical company can achieve supply chain agility is limited. Design/methodology/approach – This paper analyzes the three parts of pharmaceutical supply chain including supply of active pharmaceutical ingredient, manufacturing and distribution based on the supply chain operations reference model to assess agile supply chains by using three diverse questionnaires. In addition, to prioritize critical factors, TOPSIS (technique for order preference by similarity to ideal solution) algorithm as a common technique of multiple attribute decision-making (MADM) model has been used. Findings – Achieving supply chain agility is dependent on other capabilities; including flexibility, responsibility, competency and quickness. Findings reveal several factors identified as critical factors to being agile in each part of pharmaceutical supply chain. Research limitations/implications – This research was challenged with some limitations such as novelty of the subject in this environment, and the lake of data in this area is also another constraint. Originality/value – This is an initial and pioneering study to highlight the importance of agility concept in the pharmaceutical industry. The present study also provides a new aspect of supply chain management for such industry, and would be a good topic for further research. Finally, this study contributes to highlight and prioritize factors involved in this area.